Global incidence and trends of ocular cancer: A bibliometric analysis - Hang Xu; Alexander C. Rokohl; Xiaojun Ju; Yongwei Guo; Xincen Hou; Wanlin Fan; Ludwig M. Heindl (Advances in Ophthalmology Practice and Research)
Background: Ocular cancer represents a significant threat to vision and life among various eye diseases. Conjunctival melanoma is regarded as one of the most feared and unpredictable ocular tumors. Considering the global differences in the occurrence of ocular melanoma across different races and regions, this study provides a thorough examination of the current state of research pertaining to the epidemiology of ocular and conjunctival cancers. Methods: This bibliometrics analysis used the Web of Science Core Collection (WoSCC) to collect data from publications on the epidemiology of ocular cancer, including relevant literature from 1951 to 2024. We examined indicators including t publication counts, citation rates, and data on contributing countries, institutions, and journals. Use VOSviewer and CiteSpace for network visualization and Microsoft Excel for data management. Our analysis reveals key trends in the epidemiology of ocular cancer across countries and identifies prominent keywords. Results: A total of 406 articles on ocular cancer were identified, with significant contributions from the United States, the United Kingdom, and Germany. Denmark also plays a crucial role, particularly in conjunctival cancer research. Carol L. Shields is a leading figure widely recognized for her influential citations in ocular cancer epidemiology. The top publication platforms include the British Journal of Ophthalmology, Ophthalmic Epidemiology, and Ophthalmology. Key terms in ocular cancer research focus on prevalence, survival, and epidemiology, while conjunctival cancer studies emphasize malignant melanoma, conjunctiva, and epidemiology. Through keyword co-occurrence and burst analysis, trending topics include prevalence, risk factors, uveal melanoma, choroidal melanoma, malignant melanoma, squamous cell carcinoma, and conjunctiva. For conjunctival cancer, key research areas expected to remain prominent are cell carcinoma, management, recurrence, ocular surface squamous neoplasia, and pathology. Conclusions: This analysis represents the first comprehensive bibliometric review mapping the trends and the knowledge structure in ocular cancer research, specifically from an epidemiological viewpoint. The results meticulously explore and encapsulate the research frontiers for scholars dedicated to the epidemiology of conjunctival cancer.